2021
DOI: 10.1038/s41372-021-01213-4
|View full text |Cite
|
Sign up to set email alerts
|

The financial burden experienced by families of preterm infants after NICU discharge

Abstract: BACKGROUND AND OBJECTIVES: Describe the financial burden and worry that families of preterm infants experience after discharge from the neonatal intensive care unit (NICU). METHODS: We surveyed 365 parents of preterm infants in a cross-sectional study regarding socio-demographics, supplemental security income (SSI), and financial worry. We completed a multivariable logistic regression model to examine the adjusted association of financial worry with modifiable factors. RESULTS: We found that 53% of participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…Once discharged from the hospital, PT infants may have frequent clinic and therapy visits and often need specialized care in the home [ 65 , 66 ]. For example, in a study of PT infants up to 24 months corrected age (i.e., age corrected for prematurity), 71% of infants had at least two clinic visits per month, 60% had at least one daily prescription medication, and 20% had durable medical equipment, such as oxygen, a feeding tube, or tracheostomy [ 66 ]. Additionally, three-quarters used early intervention services that require frequent therapy encounters, averaging between 1.8 to 4.4 h of therapy per month, depending on the type of service [ 66 , 67 ].…”
Section: The Interplay Between Work and Mom Provision In Mothers Of P...mentioning
confidence: 99%
See 2 more Smart Citations
“…Once discharged from the hospital, PT infants may have frequent clinic and therapy visits and often need specialized care in the home [ 65 , 66 ]. For example, in a study of PT infants up to 24 months corrected age (i.e., age corrected for prematurity), 71% of infants had at least two clinic visits per month, 60% had at least one daily prescription medication, and 20% had durable medical equipment, such as oxygen, a feeding tube, or tracheostomy [ 66 ]. Additionally, three-quarters used early intervention services that require frequent therapy encounters, averaging between 1.8 to 4.4 h of therapy per month, depending on the type of service [ 66 , 67 ].…”
Section: The Interplay Between Work and Mom Provision In Mothers Of P...mentioning
confidence: 99%
“…For example, in a study of PT infants up to 24 months corrected age (i.e., age corrected for prematurity), 71% of infants had at least two clinic visits per month, 60% had at least one daily prescription medication, and 20% had durable medical equipment, such as oxygen, a feeding tube, or tracheostomy [ 66 ]. Additionally, three-quarters used early intervention services that require frequent therapy encounters, averaging between 1.8 to 4.4 h of therapy per month, depending on the type of service [ 66 , 67 ]. Apart from these health care needs, PT infants are susceptible to viral respiratory infections that may prevent attendance at a normal daycare facility, requiring families to utilize in-home childcare instead [ 68 , 69 ].…”
Section: The Interplay Between Work and Mom Provision In Mothers Of P...mentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of 365 parents of premature infants, only 26% of parents whose newborns were hospitalized in the NICU discussed costs of care with NICU staff and only 19% of parents discussed costs of care with their pediatrician. 10 In a recent study, the CenteringPregnancy group demonstrated a novel approach to prenatal care involving group-based education. This method resulted in significant cost savings for CenteringPregnancy, with an estimated net savings of $67 293 reduction in NICU costs for 85 patients, or an average of approximately $792 per patient.…”
mentioning
confidence: 99%
“…General pediatricians commonly feel unprepared to manage DMES and delegate DMES responsibilities to other service teams and support staff . Patients and families report substantial distress from DMES use and barriers to reliable access . While researchers recognize that DMES use can both positively and negatively affect health and health services, the lack of standardization in measuring DMES use prevents addressing important knowledge gaps.…”
mentioning
confidence: 99%